Internet routing architectures - Halabi, Sam. (Sam Halabi) (Cisco Press, 2003)
Providing information on BGP4, as well as perspectives on internetworking routing architectures, this second edition is a resource for Internet routing solutions and scenarios. It is intended for the advanced networking computer science course and is a classroom text covering protocols and routine.